Evaluación de quitomax® en la emergencia, crecimiento y nutrientes de plántulas de tomate (Solanum lycopersicum L.) - Reyes Pérez, Juan (2019)
The application of plant growth biostimulants is a very promising alternative for obtaining vigorous seedlings in a shorter time. In this work, the application of several concentrations of Quitomax® (1000, 2000 and 3000 mg.L-1) and a control treatment with distilled water to tomato seeds (Solanum lycopersicum L.) var. Amalia planted in trays with soil, was evaluated on emergence index, growth variables and nutrient contents of resulting tomato seedlings, with 15 days of age. It was evaluated emergence index of the seedlings in the time, plant growth variables root length, length and diameter of stem, fresh and dry weight of roots and foliar part (stem and leaves), as well as seedling nutrient contents of nitrogen, phosphorus, potassium, calcium and magnesium. A randomized block design was applied with three replicates per treatments. Results showed plants from seeds treated with Quitomax® had a faster emergence index, greater roots and stems, as well as, higher fresh and dry masses than the control treatment Additionally seedling from Quitomax® treatment showed higher nutrient contents than the control, while Quitomax® at 1000 mg.L-1 was the best treatment.